Development and Clinical Validation of a Rapid RPA Assay for Ehrlichia Canis Detection in Canine Blood Using Fluorescence and Lateral Flow Formats (International Journal of Environmental Sciences, 2025)
Ehrlichia canis, the causative agent of canine monocytic ehrlichiosis (CME), is a globally important tick-borne pathogen in dogs. Current diagnostic methods such as PCR require advanced laboratory infrastructure, limiting their use in field settings. This study developed and validated a dual-format recombinase polymerase amplification (RPA) assay targeting the 16S rRNA gene of E. canis, incorporating both fluorescence-based real-time detection and lateral flow strip readouts. Primers and probes were designed using Primer-BLAST and optimized for RPA at 39 °C for 20 minutes. Analytical sensitivity reached 10 femtograms of genomic DNA (~7–10 bacterial genomes), with 100% analytical specificity against related pathogens (Anaplasma platys, A. phagocytophilum, Rickettsia rickettsii). Clinical validation with 500 canine blood samples from Chennai, India, identified 43 positive cases (8.6% prevalence), achieving perfect concordance with conventional PCR (100% sensitivity and specificity; Cohen’s κ = 1.000). The fluorescence format provided semi-quantitative results with strong correlation between DNA concentration and threshold time (R² = 0.981), while the lateral flow format enabled simple visual interpretation within 30 minutes. The RPA assay demonstrated excellent reproducibility (CV < 7%), reagent stability at ambient temperature (>6 months), and ~65% cost reduction compared to PCR. These results highlight the RPA assay as a rapid, accurate, and field-deployable diagnostic tool for CME, particularly suited to veterinary practice and surveillance in resource-limited, tick-endemic regions.